Investing in young agripreneurs: Why and how? - Franzel, Steven; Davis, Kristin E.; Gammelgaard, Johanna; Preissing, John (Food and Agriculture Organization of the United Nations, 2022)
There are few wage-earning opportunities for the 223 million unemployed or underemployed youth in developing and emerging economies. Many of those young people are in rural areas where the local economy is largely agricultural. Agripreneurship – entrepreneurial activity in agriculture – increases youth employment while teaching them the hard and soft skills they need to manage enterprises profitably and sustainably. This improves their revenue, reduces business failure and fosters innovation in the agrifood systems of tomorrow. The brief explains the principles of investing wisely in such programmes for maximum benefit. This publication is part of the Investment Briefs series under the FAO Investment Centre’s Knowledge for Investment (K4I) programme.